2013
DOI: 10.1055/s-0033-1350106
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Image Quality Measurements of a Digital Breast Tomosynthesis System

Abstract: Purpose: The aim of this study was to measure the image quality of a digital breast tomosynthesis (DBT) system quantitatively. Materials and Methods: The signal transfer property (STP), modulation transfer function (MTF), noise power spectrum (NPS), and detective quantum efficiency (DQE) of the Hologic Selenia Dimensions breast tomosynthesis system were measured according to established methods. The NPS was calculated from two-dimensional (2?D) fast Fourier transform (FFT) of flat field images. The presamplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…In addition, the MTF plots appear to vary almost as a linear function of frequency. While this behavior is not typically exhibited by x-ray detectors, it is unique to the HSD system in the 2D mode, as previously reported by Olgar et al 26 Figure 6(b,c) shows the variation in the NNPS and DQE characteristics with incident air kerma. Figure 5(c) shows the simulated DQE plots compared against measured data.…”
Section: Experimental Datasupporting
confidence: 77%
“…In addition, the MTF plots appear to vary almost as a linear function of frequency. While this behavior is not typically exhibited by x-ray detectors, it is unique to the HSD system in the 2D mode, as previously reported by Olgar et al 26 Figure 6(b,c) shows the variation in the NNPS and DQE characteristics with incident air kerma. Figure 5(c) shows the simulated DQE plots compared against measured data.…”
Section: Experimental Datasupporting
confidence: 77%
“…The zero degree acquisition mode was not available on the early generation Inspiration systems and therefore there was some influence of focus motion on the DQE data in this study. The DQE data of Olgar et al (2013) for a Selenia Dimensions operated in binned zero degree mode showed that DQE was constant for DAK levels above approximately ∼13.5 μGy. Given the essentially flat NPS curves seen for a-Se based DBT systems, DQE(f) has a shape that follows ( ) MTF f 2 and therefore DQE(f) falls rapidly in binned mode compared to non-binned operation Zhao 2008a, Olgar, Kahn andGosch 2013).…”
Section: Nps Measured In the Reconstructed Planesmentioning
confidence: 96%
“…The DQE data of Olgar et al (2013) for a Selenia Dimensions operated in binned zero degree mode showed that DQE was constant for DAK levels above approximately ∼13.5 μGy. Given the essentially flat NPS curves seen for a-Se based DBT systems, DQE(f) has a shape that follows ( ) MTF f 2 and therefore DQE(f) falls rapidly in binned mode compared to non-binned operation Zhao 2008a, Olgar, Kahn andGosch 2013). Zhao et al (2015) developed a version of cascaded linear system analysis for the low and high gain modes of a CsI-CMOS x-ray detector (Dexela 2923 MAM) with emphasis on the detector electronic noise performance.…”
Section: Nps Measured In the Reconstructed Planesmentioning
confidence: 96%
“…The factors that affect the image need to be understood before simulation. Evaluations of DBT systems have been undertaken by various authors (Marshall et al 2010, Olgar et al 2013, Rodríguez-Ruiz et al 2016 and in various National Health Service Breast Screening Programme (NHSBSP) reports (www.gov. uk/government/collections/breast-screening-professional-guidance).…”
Section: Introductionmentioning
confidence: 99%